Tourism and Development 2017: Active & Sports Tourism: Feel the Freedom of the Water: Book of abstracts - Gorenak, Mitja; Trdina, Andreja (2017)
Under the title Tourism and Development 2017 – Active and Sports Tourism: Feel the Freedom of Water we have conducted the 4th annual scientific conference, organized by the three partner faculties, Faculty of Tourism of the University of Maribor, Faculty of Sports and Tourism, Educons University from Novi Sad and Libertas Business school from Zagreb. This book of extended abstracts presents a wide range of over 25 different views on three topics that were discussed at the conference. The introductory part presents short summaries of thougts discussed by our invited keynote speakers. The first section presents extended abstracts from the field of active tourism, which address the diverse aspects of active vacationing as becoming increasingly important in tourism. The second thematic section includes extended abstracts on the topic of sports tourism, a specific category of tourism that has been developing rapidly with more and more visitors coming to major international sports events and also more and more visitors actively seeking sports related vacation. The last section presents extended abstracts on accessible tourism, nowadays increasingly important area arising from the principles of ensuring equal opportunities and promoting social inclusion in tourism. All the extended abstracts provide scientific views on selected topics, and, thus, bring additional knowledge into the particular field of tourism.
Keywords: international conference; tourism; active tourism; sports tourism; accessible tourism